Protective effect of the thoracic cage on parenchyma in response to trauma direction in blunt thoracic trauma: an experimental study - Ozel, S. Kerem; Ozel, H. Banu; Colakoglu, Neriman; Ilhan, Nevin; Arslan, Nurettin; Ozan, Enver (Turkish Assoc Trauma Emergency Surgery, 2010)
BACKGROUND We aimed to investigate the protective potential of the thoracic cage on the parenchyma in response to blunt trauma from different directions in an animal model. METHODS Female Wistar albino rats were divided into control, anterolateral, lateral and posterolateral trauma groups, with six rats in each group. A weight of 500 g was dropped from a height of 40 cm on the left hemithorax to produce an energy of 1.96 joules, using a specially designed platform. Respiratory rates and heart rates were noted before and at 0, 1, and 5 minutes after trauma. Twenty-four hours later, the left lungs were excised for wet lung weight measurement, histological examinations and tissue malondialdehyde determination. RESULTS Severe pulmonary contusion was observed in all trauma groups according to histological parameters. Malondialdehyde was increased in both the lateral and posterolateral groups. Wet lung weight was increased only in the posterolateral trauma group when compared to controls. Histologically, macrophages were increased and mononuclear cell infiltration was significant in the posterolateral trauma group. There were no significant changes in physiological parameters in the groups. CONCLUSION Lung parenchyma seems to be badly affected after trauma to the posterolateral thoracic wall. Different thoracic regions may respond differently to the same traumatic stress, and this may be related to the biomechanical properties of the thoracic cage.
Künt toraks travmasinda gö?üs kafesinin travma yönüne göre parenkim koruyucu etkisi: Deneysel çalişma
Keywords: Blunt trauma; parenchymal injury; thorax